CRIMINAL VICTIMIZATION ON LARGE-SCALE INVESTMENT SCAM IN INDONESIA - Setiawan, Peter Jeremiah; Ardison, Hansel (Veritas et Justitia, 2021)
Mass scale investment fraud (Ponzi) schemes result in protracted suffering for the victims.  In this article the author investigates this crime from a juridical normative, case, and conceptual approach.  From the very start potential victims may fall to promises of lucrative and safe investment schemes. In the eyes of the more prudent, it would or should be obvious that the collaborative business offers as presented contains logical flaws, running against common sense and is at the outset illegal. Notwithstanding, victims seems to fall easily into this trap, lured by the promise of getting easy, quick, and huge investment returns.  In the end, even when this fraudulent investment scheme unravels, the government of law enforcement seems to be unable to act decisively and offer a satisfactory solution. Slow and ineffective government response in the end exacerbate economic loss and victims suffering.